Land Price Distortion, Financial Development, and Regional Innovation - Pengcheng Zhou; Ruiqi Qin; Baitang Luo; Hao Wen (Discrete Dynamics in Nature and Society)
As an important tool for local governments to implement regional development policies, the allocation of land resource plays an important role in promoting regional innovation and development. Based on the microdata of land transfer in 287 cities in China from 2007 to 2017, this study examines the relationship between land price distortion, regional financial development, and regional innovation ability. The results show that land price distortion promotes the improvement of regional innovation ability. There is a significant time-lag effect because it is mainly realized by increasing the fiscal revenue of local governments and providing implicit subsidies to enterprises. The larger the financial scale is, the better the financial structure is and the higher the financial efficiency will further strengthen such a positive effect. Further analysis shows that the impact of land price distortion on improving regional innovation ability is significantly different between central or western regions and the eastern regions. This study provides empirical evidence for promoting regional innovation ability by land price distortion, which is conducive to a better understanding of the importance of reasonable land resource allocation and financial market development in the process of high-quality economic development, providing a useful insight into China’s future reform of land market and financial market.